Industry 4.0 in Finance, Digital Financial Services and Digital Financial Inclusion in Developing Countries: Opportunities, Challenges, and Possible Policy Responses - Mpofu, Favourate Y. (International Journal of Economics and Financial Issues, 2024)
Fintech and the adoption of Fourth Industrial Revolution (industry 4.0) technologies have expanded the provision and uptake of digital financial services (DFSs) globally. Digital transformation in the financial industry intended to modify financial service provisioning by reducing the costs of accessing and challenges such as inaccessibility due to remoteness, not having a bank account, not having a credit history, or having erratic incomes. Digital financial inclusion (DFI) aims to ensure that financial services, such as deposits, payments, transfers, withdrawals, investments, accessing insurance and credit, checking account balances, receiving money, and making international remittances, are conducted conveniently, easily, safely, reliably, and affordably. DFI focuses on ensuring access to financial services through digital channels and platforms for individuals, businesses, and households, to promote financial inclusion for all stakeholders, especially previously financially excluded groups. Through a critical review of the literature, this study explores the opportunities and challenges of DFI or the adoption and use of DFS. The review unpacks the possible benefits of using DFSs, which include the broadening financial inclusion, increasing diversity and innovation in the financial services sector, attainment of the SDGs, reduction of poverty, increased economic growth, and minimization of the gender financial inclusion gap, as well as reduction in inequalities. The constraints include the inadequacy of digital infrastructure, taxes on DFS, literacy challenges, digital exclusion, poverty and the gender divide, risks, and lack of trust in the financial services sector. The study recommends appropriate regulation and oversight, literacy enhancement initiatives, investment in digital infrastructure, and increased consumer protection as measures to improve DFI in developing countries.